Sustainability of the Theories Developed by Mathematical Finance and Mathematical Economics with Applications - Wong, Wing-Keung (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The topics studied in this Special Issue include a wide range of areas in finance, economics, tourism, management, marketing, and education. The topics in finance include stock market, volatility and excess returns, REIT, warrant and options, herding behavior and trading strategy, supply finance, and corporate finance. The topics in economics including economic growth, income poverty, and political economics.